Penerapan Model Kooperatif Tipe TGT Menggunakan Media Interaktif Berbasis Wordwall terhadap Mata Pelajaran IPAS kelas IV - Andini, Sonia Putri; Egok, Asep Sukenda; Raflesia, Citra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the learning outcomes of science learning in grade IV of SD Negeri 07 Bingin Teluk after implementing the TGT-type cooperative model using interactive media, based on whether word walls were significantly completed. This research method used a pre-experimental design; the research design is a one-group pretest-posttest. The study's results showed the results of the initial test (pre-test) with an average pre-test value of 45.53 and an average final test (post-test) value of 72.81. This shows that the average value of the final test (post-test) is greater than the initial test (pre-test). After being calculated using the t-test, the t_count value (4.15) was obtained which was compared with the 〖 t〗_table value with a significance level of 5% was (1.695). So the t_count value > 〖 t〗_table or 4.15 > 1.695. In conclusion, the science learning outcomes of fourth-grade students at SD Negeri 07 Bingin Teluk after implementing the TGT cooperative learning model using interactive wordwall-based media significantly improved by the 2025 academic year. Keywords: Wordwall Media, Science Learning, TGT Model Implementation